2021
DOI: 10.1021/jasms.1c00273
|View full text |Cite
|
Sign up to set email alerts
|

Collision-Induced Unfolding of Native-like Protein Ions Within a Trapped Ion Mobility Spectrometry Device

Abstract: Native mass spectrometry and collision-induced unfolding (CIU) workflows continue to grow in utilization due to their ability to rapidly characterize protein conformation and stability. To perform these experiments, the instrument must be capable of collisionally activating ions prior to ion mobility spectrometry (IMS) analyses. Trapped ion mobility spectrometry (TIMS) is an ion mobility implementation that continues to grow in utilization due to its inherently high resolution and reduced instrumental footprin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 60 publications
7
44
2
Order By: Relevance
“…Higher collision voltages cause unfolding of the protein, resulting in the observed increases in CCS until a plateau is reached around 1900 Å 2 , a rather modest 10% increase in CCS. The general CIU profile mirrors one shown in a recent ion mobility/CIU study of cytochrome c (7+ charge state), in which the CCS of the folded protein was 1503 Å 2 prior to exhibiting a transition at higher collision voltages to adopt a series of unfolded structures of around 1950, 2000, and 2100 Å 2 , net increases of 30 to 40% . While it appears that the CIU experiments in the Orbitrap mass spectrometer do not result in the same extent of unfolding as IM experiments, the results are not expected to be identical owing to the difference in the experimental details.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Higher collision voltages cause unfolding of the protein, resulting in the observed increases in CCS until a plateau is reached around 1900 Å 2 , a rather modest 10% increase in CCS. The general CIU profile mirrors one shown in a recent ion mobility/CIU study of cytochrome c (7+ charge state), in which the CCS of the folded protein was 1503 Å 2 prior to exhibiting a transition at higher collision voltages to adopt a series of unfolded structures of around 1950, 2000, and 2100 Å 2 , net increases of 30 to 40% . While it appears that the CIU experiments in the Orbitrap mass spectrometer do not result in the same extent of unfolding as IM experiments, the results are not expected to be identical owing to the difference in the experimental details.…”
Section: Resultssupporting
confidence: 62%
“…In conventional IM CIU methods, collisional heating occurs immediately prior to the ions’ transit through the drift cell. Even aside from CIU studies, there is a large spread in IM-CCS values reported for native-like folded cytochrome c (7+), ranging from 1503 ( ) to 1790 Å 2( ) and others in-between. , The ability to monitor CIU of native-like proteins offers another avenue for capitalizing on the measurement of CCS values in an Orbitrap analyzer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In doing so, we consistently observe native like arrival time distributions for small proteins such as ubiquitin and cytochrome c. , Since the gas phase lacks solvent and, thus, refolding back into the native structure can be considered highly unlikely, approaches such as gas-phase simulated annealing MD performed at much higher temperatures might be expected to give artifactual results for well-folded proteins. Indeed, an increase in the temperature (i.e., through collisional activation) of compact cytochrome c structures in the gas phase with cyclic tandem mobility experiments and trapped ion mobility experiments does produce extended states that do not compact down to the original CCS values, with the compact structures displaying a “permanent” increase in CCS. , With these considerations, the most accurate modeling of gaseous structures of well-folded proteins would need to keep temperatures low enough that the gas-phase rearrangement barriers are not reached. Additionally, using the crystal structure of folded proteins, followed by relaxation in the gas phase, accurately reproduces experimental observables. , …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, an increase in the temperature (i.e., through collisional activation) of compact cytochrome c structures in the gas phase with cyclic tandem mobility experiments and trapped ion mobility experiments does produce extended states that do not compact down to the original CCS values, with the compact structures displaying a "permanent" increase in CCS. 62,63 With these considerations, the most accurate modeling of gaseous structures of well-folded proteins would need to keep temperatures low enough that the gas-phase rearrangement barriers are not reached. Additionally, using the crystal structure of folded proteins, followed by relaxation in the gas phase, accurately reproduces experimental observables.…”
Section: ■ Results and Discussionmentioning
confidence: 99%